Modification of the physical and chemical properties of Inpago-Protani rice flour via fermentation with Bimo-CF starter - Aini, Nur; Arsyistawa, Hadana Sabila; Sustriawan, Budi; Prihananto, Vincentius; Astuti, Santi Dwi; Septiana, Aisyah Tri; Indarto, Indarto; Suliman, Nageeb Mohammed (Department of Technology of Agricultural product (THP) Jambi University, 2024)
Inpago-Protani rice is a new rice variety from Jenderal Soedirman University, Indonesia. Producing rice flour as an intermediate product is a practical rice processing method. However, the utilization of rice flour as a wheat flour alternative is limited due to the differences in their gelatinization qualities. Fermentation with Lactobacillus sp. changes the gelatinization properties of rice flour by increasing the number of microorganisms and stimulating their metabolism in food materials. This study sought to determine how the physical and chemical qualities of Inpago-Protani rice flour are affected by the duration of fermentation, the concentration of Bimo-CF starter, and other factors. Applying 0.6% Bimo-CF starter for 12 hours at 30°C was the most effective method for fermenting Inpago-Protani rice flour. The resulting rice flour had a yield of 40.3%, a protein content of 10.3% (db), a carbohydrate content of 77.1%, a fat content of 0.4%, an ash content of 0.5%, a moisture content of 12.2%, and 338.7 kcal of energy. The enhanced characteristics of fermented rice flour may increase its versatility for subsequent processing.